A Cost-Effectiveness Analysis of Stop Smoking Interventions in Substance-Use Disorder Populations. Issue 5 (4th May 2018) - Healey, Andrew; Roberts, Sarah; Sevdalis, Nick; Goulding, Lucy; Wilson, Sophie; Shaw, Kate; Jolley, Caroline; Robson, Deborah
Abstract: Background: Tobacco smoking is highly prevalent among people attending treatment for a substance-use disorder (SUD). In the United Kingdom, specialist support to stop smoking is largely delivered by a national network of stop smoking services, and typically comprises of behavioral support delivered by trained practitioners on an individual (one-to-one) or group basis combined with a pharmacological smoking-cessation aid. We evaluate the cost-effectiveness of these interventions and compare cost-effectiveness for interventions using group- and individual-based support, in populations under treatment for SUD. Methods: Economic modeling was used to evaluate the incremental cost-per-quality-adjusted-life-years (QALYs) gained for smoking-cessation interventions compared with alternative methods of quitting for the SUD treatment population. Allowance was made for potentially lower abstinence rates in the SUD population. Results: The incremental cost-per-QALY gained from quit attempts supported through more frequently provided interventions in England ranged from around £4, 700 to £12, 200. These values are below the maximum cost-effectiveness threshold adopted by policy makers in England for judging whether health programs are a cost-effective use of resources. The estimated cost-per-QALY gained for interventions using group-based behavioral support were estimated to be at least half the magnitude of those using individual support due to lower intervention costs and higher reported quit rates. Conclusions reached regarding the cost-effectiveness of group-based interventions were also found to be more robust to changes in modeling assumptions. Conclusions: Smoking-cessation interventions were found to be cost-effective when applied to the SUD population, particularly when group-based behavioral support is offered alongside pharmacological treatment. Implications: This analysis has shown that smoking-cessation interventions combining pharmacological treatment with behavioral support can offer a cost-effective method for increasing rates of smoking cessation in populations being treated for a substance-use disorder. This is despite evidence of lower comparative success rates in terms of smoking abstinence in populations with SUD. Our evaluation suggests that medication combined with group-based behavioral support may offer better value for money in this population compared with interventions using individual support, though further evidence on the comparative effectiveness and cost of interventions delivered to SUD treatment populations would facilitate a more robust comparison.